SEJARAH LAHIRNYA GERAKAN PEMUDA ANSOR PADA ORGANISASI MASYARAKAT NAHDLATUL ULAMA - Zudi Setiawan (Universitas Wahid Hasyim Semarang, 2022)
The history of the birth of the Ansor Youth Movement (GP Ansor) cannot be separated from the long history of the birth and movement of the community organization Nahdlatul Ulama (NU). The birth of GP Ansor was also driven by conditions in the Dutch East Indies at that time, where regional youth organizations had emerged such as Jong Java, Jong Ambon, Jong Sumatra, Jong Minahasa, Jong Celebes, and others. The birth of GP Ansor was colored by the spirit of the nationalism movement to fight for the nation's independence. GP Ansor was born in an atmosphere of integration between the pioneering youth after the Youth Pledge (Sumpah Pemuda), the spirit of nationalism, democracy, and at the same time the religious spirit of Islam.Keywords: History, Community Organization, Ansor Youth Movement, Nahdlatul UlamaAbstrakSejarah lahirnya Gerakan Pemuda Ansor (GP Ansor) tidak bisa dilepaskan dari sejarah panjang kelahiran dan gerakan organisasi masyarakat (ormas) Nahdlatul Ulama (NU). Kelahiran GP Ansor juga didorong oleh kondisi di Hindia Belanda pada saat itu, di mana-mana telah muncul organisasi pemuda yang bersifat kedaerahan seperti Jong Java, Jong Ambon, Jong Sumatera, Jong Minahasa, Jong Celebes, dan lain-lain. Kelahiran GP Ansor diwarnai oleh semangat pergerakan nasionalisme untuk memperjuangkan kemerdekaan bangsa. GP Ansor terlahir dalam suasana keterpaduan antara kepeloporan pemuda pasca-Sumpah Pemuda, semangat kebangsaan, kerakyatan, dan sekaligus spirit keagamaan Islam.Kata Kunci: Sejarah, Organisasi Masyarakat, Gerakan Pemuda Ansor, Nahdlatul Ulama